A mechanism for chronic filarial hydrocele with implications for its surgical repair. - Joaquim Norões; Gerusa Dreyer (Public Library of Science (PLoS), 2010)
BACKGROUND: Chronic hydrocele is the most common manifestation of bancroftian filariasis, an endemic disease in 80 countries. In a prospective study, we evaluated the occurrence of intrascrotal lymphangiectasia, gross appearance/consistency of the testis, and the efficacy of complete excision of hydrocele sac in patients living in a bancroftian filariasis endemic area who underwent hydrocelectomy at the Center for Teaching, Research and Tertiary Referral for Bancroftian Filariasis (NEPAF). METHODOLOGY/PRINCIPAL FINDINGS: A total of 968 patients with uni- or bilateral filarial hydrocele (Group-1) and a Comparison Group (CG) of 218 patients from the same area who already had undergone hydrocele-sac-sparing hydrocelectomy elsewhere were enrolled at NEPAF. Twenty-eight patients from the Comparison Group with hydrocele recurrence were re-operated on at NEPAF and constitute Group-2. In Group-1 a total of 1,128 hydrocelectomies were performed (mean patient age of 30.3 yr and mean follow-up of 8.6 yr [range 5.3-12]). The hydrocele recurrence rates in Group-1 and in the Comparison Group (mean age of 31.5 yr) were 0.3%, and 19.3%, respectively (p<0,001). There was no hydrocele recurrence in Group-2 (mean patient age of 25.1 yr and mean follow-up of 6 yr [range 5-6.9]). Per surgically leaking or leak-prone dilated lymphatic vessels were seen in the inner or outer surface of the hydrocele sac wall or in surrounding tissue, particularly in the retrotesticular area, in 30.9% and in 46.3% of patients in Group-1 and Group-2, respectively (p = 0.081). The testicles were abnormal in shape, volume, and consistency in 203/1,128 (18%) and 10/28 (35.7%) of patients from Group-1 and Group-2, respectively (p = 0,025). CONCLUSIONS/SIGNIFICANCE: Lymph fluid from ruptured dilated lymphatic vessels is an important component of chronic filarial hydrocele fluid that threatens the integrity of the testis in an adult population living in bancroftian filariasis endemic areas. To avoid hydrocele recurrence the authors advise complete excision of hydrocele sac and when identified, leaking or leak-prone dilated lymphatic vessels should be sutured or excised.